USING DIGITAL TECHNOLOGIES IN DEVELOPING STUDENTS' SKILLS IN USING PEDAGOGICAL TAXONOMY (Universal International Scientific Journal, 2026)
This article analyzes the importance and potential of digital technologies in the process of developing students' skills in using pedagogical taxonomy. The widespread use of information and communication technologies in the modern education system is an important factor in the effective organization of the educational process, activating students' thinking activities, and forming their independent learning skills. The article highlights the advantages of using digital platforms and tools in the process of designing the educational process, determining learning goals, and assessing them based on pedagogical taxonomy.
Keywords: pedagogical taxonomy, digital technologies, educational process, interactive methods, digital educational resources, innovative education, competence.